(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
The main objectives of this paper are: To identify and examine how Chinua Achebe presents the concept of alienation and identity crisis in Things Fall Apart and to examine the experiences of the major characters in the novel and extract lessons learnt. Achebe focuses on tradition/modernity dichotomy and the conflict between traditional way of life and the modern way brought by the British. Literature has the ability of recording the characteristics of times including the social manners, customs, how people act and react, what they do, think, like and dislike. In Things Fall Apart, the way people act and react leads to alienation and identity crisis. Things Fall Apart provides us with social pictures of whole societies through the story of Okonkwo. The novel derives its strength from the quality of its writer’s understanding of the social forces at work at the time and the way he uses his knowledge of human psychology to develop his central character who is Okonkwo. The novel dramatises how conditions are changing around the protagonist especially in the social sphere bringing about many changes in the attitudes of people towards many issues